Study on a New Environmentally Friendly Synthetic Fluid for Preparing Synthetic-Based Drilling Fluid - Sun, Yuxue; Zhu, Xiuyu; Zhao, Jingyuan; Sui, Dianjie (Frontiers in Chemistry, 2020)
In view of the pollution problems related to using oil-based drilling fluids, we prepared a new environmentally friendly synthetic fluid, namely, NSF, for use in synthetic-based drilling fluid instead. We used heavy hydrocarbons from Daqing as raw material in our preparation and employed few-steps refining techniques such as hydrodesulfurization, hydrodearomatization and hydrogenation. After the treatment, the sulfur and aromatic hydrocarbon contents in the NSF were less than 0.5 mg/L, meeting international environmental standards. NSF is composed mainly of C12-C22 hydrocarbons, and is characterized by low impurity content, small specific gravity, and easy degradation. In addition, the LC50 value is greater than the 1 000 000 mg/L water-soluble fraction; therefore, its toxicity is less than 10 percent of that of diesel in oil-based drilling fluid and, as the flash point of NSF is about 134 ℃, the related fire hazard is low. The synthetic-based drilling fluid with NSF has the advantage of causing no swelling damage to the reservoir, and saves the cost of drilling fluid because it doesn’t need to deal with the environmental problems (the sulfur and aromatic hydrocarbon contents were less than 0.5 mg/L) and field problems caused by the reaction between drilling fluid and reservoir, and greatly increases the ROP through reducing the drill pipe sticking and with C12-C22 hydrocarbons in synthetic-based fluid, and safely uses, and has stable drilling fluid performances which are flash point(134 ℃) and low fire hazard. We have therefore achieved our aim of preparing a high-quality and non-toxic synthetic fluid, of which the aromatic hydrocarbon and sulfur contents meet international standards. Using this synthetic-based drilling fluid therefore facilitates environment protection drilling.